Wastewater engineering : - Tchobanoglous, George (McGraw-Hill, 1991)
The book offers the knowledge of the environmental effects of wastewater discharges; reflects the impact of changing federal legislation on water quality control and sludge management; provides information on other types of wastewater systems, such as small systems and overflows from combined sewers